2019
DOI: 10.1093/ofid/ofz141
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tubular Necrosis Associated With High Serum Vancomycin and Tobramycin Levels After Revision of Total Knee Arthroplasty With Antibiotic-Containing Calcium Sulfate Beads

Abstract: We present the case of a 59-year-old male who developed acute tubular necrosis with a serum tobramycin level of 15.9 mg/L after instillation of tobramycin and vancomycin calcium sulfate beads for infected total knee arthroplasty. We emphasize standardizing surgical protocols to mitigate nephrotoxicity based on current efficacy and safety data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Additionally, IO antibiotics are more effective than IV use to inhibit the risk of Gram-positive bacteria. In patients with joint replacement, the incidence of AKI ranges from 1% to 20%, and after IO use, the vancomycin concentration in the serum was lower than that of the venous concentration, and so it has less effect on renal function ( 19 , 20 , 21 ). However, our study found no difference in the incidence of AKI between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IO antibiotics are more effective than IV use to inhibit the risk of Gram-positive bacteria. In patients with joint replacement, the incidence of AKI ranges from 1% to 20%, and after IO use, the vancomycin concentration in the serum was lower than that of the venous concentration, and so it has less effect on renal function ( 19 , 20 , 21 ). However, our study found no difference in the incidence of AKI between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, renal function without dialysis improved. [11] It is interesting to note that the company that produces Stimulan® beads does not support the addition of antibiotics to its bone filler product. However, tobramycin is listed in 2 doses on the product insert: 240 mg for the reconstituted intravenous solution and 1.2 g for the powder formulation.…”
Section: The Authors Have No Funding and Conflicts Of Interest To Dis...mentioning
confidence: 99%
“…The rate of AKI has been associated with patient comorbidities [18,19]. A large contributor to that incidence is patients who have high serum concentrations of vancomycin [20], as well as in those who receive dual antibiotic prophylaxis (cefazolin and vancomycin) [21]. IO administration of vancomycin after tourniquet inflation has been shown to keep serum concentrations nondetectable during surgery [3].…”
Section: Type Of Complicationmentioning
confidence: 99%